Asymmetric Impact of Public Service Digitalization on Local Economic Productivity Transformation in Rural Indonesia - Mutiara Shifa; Sri Maryanti; Dian Ariani; Ngurah Pandji Mertua Agung Durya; Sugeng Karyadi (Indonesian Journal Economic Review (IJER), 2026)
This study examines the asymmetric impact of public service digitalization on the transformation of local economic productivity in rural areas of Indonesia. Digitalization of public services is expected to improve efficiency, accessibility, and transparency; however, its benefits are not always evenly distributed across regions and communities. Using a quantitative approach, this research analyzes how variations in digital access, digital service utilization, institutional capacity, and human capital shape local economic productivity outcomes. Primary data were collected through a structured questionnaire from 100 respondents representing rural micro-entrepreneurs, community leaders, and local public service users. Data were analyzed using SPSS with multiple linear regression techniques. The results indicate that public service digitalization has a significant positive effect on local economic productivity, but the magnitude of its impact differs depending on digital literacy levels and infrastructure readiness. Digital access and service utilization significantly enhance productivity, while institutional capacity strengthens the effectiveness of digital transformation. Conversely, limited human capital creates an asymmetric effect, constraining productivity gains in less-prepared rural areas. Simultaneous testing confirms that all independent variables collectively influence local economic productivity. These findings highlight that digital transformation in rural public services must be accompanied by inclusive capacity-building policies to avoid widening productivity gaps. The study contributes to the literature on digital governance and rural economic development by providing empirical evidence from a developing country context.